2020
DOI: 10.1002/2211-5463.12990
|View full text |Cite
|
Sign up to set email alerts
|

Identification and analysis of micro‐exons in AP2/ERF and MADS gene families

Abstract: Micro-exons are a set of ultrashort exons with lengths ≤ 51 nucleotides. Our previous study revealed that micro-exons were enriched in AP2 domains and K-box domains, which are crucial components of AP2/ERF (APETALA2/ethylene-responsive element-binding protein) and MADS-box (an acronym of MCM1, AGAMOUS, DEFICIENS and SRF) genes, respectively. In this study, we analyzed micro-exons in the AP2/ERF family from 63 species and demonstrated that 76.8% of micro-exons are concentrated in AP2 domains. Most micro-exons a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 44 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…88% of micro-exons were contributed by the AP2 subfamily in the sesame pan-genome with only 15 out of 128 identified genes lacking micro-exons. Song et al, 2020, also reported that AP2 micro-exon genes are highly conserved which we found only to be partially true in the pan-genome. 44% of micro-exon genes were conserved in the pan-genome in the AP2 sub-family whereas the extent was higher in the Chinese accessions particularly in landraces Baizhima and Mishouzhima, wherein 83% sequence conservation was observed.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…88% of micro-exons were contributed by the AP2 subfamily in the sesame pan-genome with only 15 out of 128 identified genes lacking micro-exons. Song et al, 2020, also reported that AP2 micro-exon genes are highly conserved which we found only to be partially true in the pan-genome. 44% of micro-exon genes were conserved in the pan-genome in the AP2 sub-family whereas the extent was higher in the Chinese accessions particularly in landraces Baizhima and Mishouzhima, wherein 83% sequence conservation was observed.…”
Section: Discussionmentioning
confidence: 58%
“…The exonic fragments of length <51bp were classified as microexons (Song et al, 2020) and we found 227 micro-exons in the sesame pan-genome varying in size from 3bp to 50 bp (SI-3A, SI-3B, SI-4 and SI-6). AP2/ERF gene family had 195 micro-exons distributed along 133 genes with Swetha contributing a major share of 36.…”
Section: Micro-exons In Sesame Pan-genomementioning
confidence: 89%
See 2 more Smart Citations
“…It was observed that A1, A4, and A5 classes are more closely related, while A2 and A6 classes shared a combined clade due to the same conserved motifs. The AP2 domain consists of one alpha helix made up of 18 amino acids that assist in the interactions of DREB genes with other proteins, followed by three antiparallel beta sheets on the major groove of the DNA ( Song et al., 2020 ). The identified 20 motifs in the Sl DREB sequences have a variable composition that is the possible reason for the classification of DREB genes into different classes with high structural resemblance with the AP2 domain.…”
Section: Discussionmentioning
confidence: 99%